Influence of different stakeholders on first-tier suppliers' sustainable supplier selection: insights from a multiple case study in the automotive first-tier industry - Sabrina Lechler; Angelo Canzaniello; Anton Wetzstein; Evi Hartmann (Business Research, 2020)
Public and academic attention towards sustainably managing companies and corresponding supply chains has been gaining significant momentum in recent years. While extensive literature is available on corporate sustainability and the original equipment manufacturers' (OEMs) downstream supply chains, there is little empirical knowledge concerning why first-tier (FT) suppliers in the upstream supply chain implement sustainability into their supplier selection (SS) processes. However, FT suppliers have a crucial role in ensuring sustainability in upstream supply chains, as they are a key transmitter and often accountable for their OEMs' subsupplier portfolios. Grounded on a cross-case study approach of five FT suppliers, two associations and three non-governmental organizations (NGOs) as well as stakeholder theory, this paper investigates how different stakeholder groups are influencing the integration of sustainability aspects into FT suppliers' SS processes. Therefore, government, NGOs, OEMs and employees are investigated as stakeholder groups. Characteristics, such as FT suppliers' size, legal structure, material criticality, employees' distance to the supply chain function, company culture and industry culture, could be identified as factors that influence the urgency of stakeholders' sustainability claims and thus FT suppliers' perceived sustainability pressure. Moreover, with regard to the OEM stakeholder group, it was found that, depending on the urgency of OEMs' sustainability claims, FT suppliers align their sustainable SS processes to the actions and expectations of different stakeholder groups and thus fulfill the OEM's sustainability expectations to varying degrees. Thus, our study contributes empirical knowledge to this so far underrepresented research field and is moreover beneficial for decision makers.
Keywords: 650; Sustainable supplier selection; Supplier management; Stakeholder theory; First-tier supplier; Case study research